Coulomb Stress Analysis of Halmahera Earthquake on June 7th 2016, Mw=6.3 and Its Correlation with Aftershocks - Fathony Akbar Pratikno; Gazali Rachman; Bagus Jaya Santosa (IPTEK The Journal for Technology and Science, 2019)
Main earthquake with magnitude Mw 6.3, has been occurred in the West of Halmahera Island, Northern Molucca on June 7th, 2016. The activity of the Pacific plate, Eurasia plate and Indo-Australia plates trigger some earthquake around Halmahera. The purpose of the current study was to determine the Coulomb stress change of the main earthquake and predict the aftershocks’ location around it. For understanding an interaction of the faults, this study used Coulomb stress change model. Three component seismic waveform data recorded by TNTI station within 132 km, SANI station within 381.2 km, LUWI station within 478.3 km, and TOLI2 station within 617.6 km of the epicenter. This study used software ISOLA-GUI to obtain the parameters of the earthquake source. The parameters of the earthquake source were then used to determine fracture orientation, length, width and slip displacement. It was also used to calculate the Coulomb stress changes around the main shock, using software Coulomb 33. The result shows that the orientation of the earthquake fault has a dip angle of 48° to the horizontal plane and has a strike of 210° against the North. The fault length is 19.49 km, the fault width is 11.59 km and slip displacement is 49.43 cm. Based on plotting result, the main earthquake in Northern Molucca on June 7th, 2016 has positive Coulomb stress change that spread across the Northeast to the Southwest. This change is likely triggered three aftershocks with a range of Mw 4.7 to 6.2.